Intercropping of hybrid maize with short duration vegetables at hill valleys of Bandarban (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted at farmer’s field in Bandarban sadar areas daring rabi season 2004-05 and 2005-06 to find out the feasibility and profitability of growing short duration vegetables i.e., Potato (var. Heera,), lalsak (var. Red king,), spinach (var. local), and French bean (var. BARI Jharseem-2) with hybrid maize (var. Pacfic-11). The grain yield of sole maize was 9.65 t/ha whereas yield reduction was found in intercrop situation The maize equivalent yield showed that maize + spinach produced significantly higher yield (15.62 t/ha) followed by maize + lalsak (14.48 t/ha) and maize + potato (13.93 t/ha). Maize + spinach recorded the highest gross margin (Tk. 86,257/ha), but higher benefit cost ratio and marginal rate of return was accounted from maize + lalsak combination. The lowest gross margin was obtained from sole maize. It revealed that the combination of maize with lalsak or spinach were more compatible and profitable intercropping system in hill valleys of Bandarban areas. Key Words: Intercropping; hybrid maize; short duration vegetables; profitable; hill valleys. DOI: 10.3329/bjar.v34i1.5753Bangladesh J. Agril. Res. 34(1) : 51-57, March 2009